This Third Wage-Labour Unrest and Industrial Conflict in Canada : 1900-1967 - Jamieson, Stuart (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author investigates the strikes and labour unrest, and the associated widespread violence and illegality in the mid-sixties ; is this a new trend on the Canadian industrial relations scène ? It is seen as the crest of the third wave of Canadian labour unrest since 1900. The author supports the main recommendations in the Woods' Report that directly concern the question of labour unrest and industrial conflict.